Peran Storytelling dalam Membentuk Narasi yang Berdampak pada Era Digital - Wahyudi, Suryadi Ali; Praptiningsih , Novi Andayani; Hayat, Heni (KOMUNIKA, 2025)
Storytelling, particularly in the form of digital storytelling, has evolved into a highly effective tool for building emotional connections and influencing audience decisions in the digital age. This study aims to analyze the role of storytelling in shaping audience perception and decisions, as well as the essential elements in digital storytelling. The method used is a literature review analyzing various sources related to digital storytelling, storytelling techniques, and its impact on social media audiences. The findings show that elements such as exposition, triggering actions, climax, falling actions, and resolution play a significant role in effectively conveying messages and capturing the audience's attention. Techniques such as the use of voice, vocal and body expressions, verbal imagery, and facial animation have been shown to enrich the audience experience and increase engagement on social media. Additionally, storytelling proves to be effective in simplifying complex messages, building emotional connections, and facilitating audience decision-making. In conclusion, storytelling is an effective tool for building personal branding, increasing audience interaction, and driving actions such as purchases or donations on digital platforms.